Model Kinerja Rantai Pasokan Komoditas Padi di Desa Rasi Kabupaten Minahasa Tenggara - Rofelia A. Hansun; Harry J. Sumampouw; Henny S. Tarore (JURNAL ADMINISTRASI BISNIS, 2018)
This research is based on the existing phenomenon, namely the performance of the supply chain of rice commodities. The purpose of this study was to determine how effective and efficient the performance of the supply chain of rice commodities in competing and meeting market needs. And the object of this research is Rasi Village, Southeast Minahasa Regency. This study aims to answer the problems or phenomena mentioned above. This research is a qualitative descriptive study with a sample of 10 samples from 10 rice farmer groups. In this study using two variables, namely (supply chain performance) and (ricecommodity). To overcome some uncertainty, there needs to be a strategy in supply chain management so that efficiency can be achieved. The results showed that the supply chain of rice commodities was quite effective but not yet efficient because there were still materials in the form of raw materials (fertilizers) that were still not well organized(limited). So in this study it can be concluded that the supply chain of rice is strongly influenced by fertilizer because fertilizer is a nutrient for the crop and its function is very important to increase the yield of rice plants as well as fertilizers that support success in the cultivation of crops in producing quality products and able to compete.Keywords: performance of Supply Chain, rice commodity